Investing into the Preliminary Sections of the Research Paper: Is the Game Worth the Candle? - Katkuvienė, Laima Erika (Kalbotyra, 2008)
Currently the research paper (RP) is the central genre of many (perhaps all) disciplines at university level. Writing a research paper is no easy undertaking for L1 students and it goes without saying that it is one of the most demanding and time-consuming assignments for EFL students. Recent years have seen increased attention being given to RP writing, however, the focus is typically on what is called the body of the RP. For example, in his Genre Analysis Swales presents his famous IMRD pattern of an RP (1998, 133-7) and the CARS model of the introduction (ibid., 222-4) but the preliminaries (except abstracts) are not included there (by preliminaries I mean titles, abstracts, acknowledgements, and outlines). True, he did investigate titles in an appendix of the book, but not acknowledgements or outlines. Typically prelims receive scant attention during practical RP writing courses as well since many teachers consider investigation into their properties merely a waste of valuable time. The purpose of this article is to discover to what extent EFL students are familiar with different patterns of composing prelims and what problems they encounter. On the basis of the findings I expect to demonstrate that the preliminary sections of an RP (which are sometimes referred to as minor genres or subgenres) deserve attention and require considerable rhetorical expertise since there is more to them than meets the eye. The corpus of the investigation is drawn from the texts of BA and MA theses composed by students of the English Philology Department, Vilnius University, in the year 2003-2006 and consists of 136 titles. To illustrate new developments in the area of composing RP titles texts of expert writers were used (examples (9), (10), (15), (16), (17), (18), (19)). Due to the limited scope of the article the analysis will concern only titles and outlines. First I will investigate titles with a special focus on the following points: importance of RP titles; functions of RP titles; their syntactic and structural properties; language points; emerging trends and fashions in the area; frequency of occurence of specific title patterns in students’ texts. The next section will be devoted to problems concerning effective outlining including the rules to observe with reference to content and the rules to observe with reference to structure. Why are RP titles important? Even though they consist, at best, of two or three lines, they play a significant role in the reception of the text, since the audience bases their decisions whether to read further basically on the title, outline, and the abstract. According to Swales, ‘it comes as little surprise that composing the few words of a title can take up inordinate amount of time, discussion, and mental effort’ (1998, 223).